Developing the leader within you 2.0 - Maxwell, John C. 1947- (Harper Collins Leadership, an imprint of HaperCollins, 2018)
With more than 80 percent of the content revised this new edition delivers the foundational principles Maxwell has used in leadership for more than forty years and includes two completely new chapters. No matter your leadership arena -business, nonprofit, education, church, or family- the principles Maxwell shares will positively impact your life and the lives of everyone around you.